Folk songs with short stories which are told related to Karaca O?lan - Şimşek, Esma (My University, 2007)
It is still obvious that there are too many unknowns about the life of the famous minstrel, Karaca O?lan in the region of Çukurova. His poems were the main subject of the common talks and had come up to now. There had been a lot of beliefs, myths and stories related to Karaca Oglan among people. In this article, we will tackle on the stories about Karaca O?lan. We can classify Karaca O?lan's poems and stories under three main topics, such as; 1. Great Folk Stories: "Karaca O?lan and İsmikan Sultan" and "Karaca O?lan" stories. In one part of the story "Han/Hal/ Nar Mahmut", Karaca O?lan is acted as a protector. 2. Printed Stories: The stories which were afterwards written by some authors according to Karaca O?lan's poems. Such as, "Karaca O?lan and Spotted Girl", "Karaca O?lan and Plateou beauty", "Karaca O?lan and Karaca Kiz", "Karaca O?lan and Bride Elif" and "Karaca O?lan's Love Adventures". 3. Folk Songs With Stories: Short stories which were formed in accordance with one or more folk songs. They are called "Şerküşte or "Kaside" in the East Anatolian region and "Bozlak" in the South Anatolia. There are also some folk songs about the adventures of Karaca O?lan. In our article, the stories in the third group are going to be handled in various cases.
Karaca O?lan' a ba?li olarak anlatilan kisa hi?kâyeli? türküler
Keywords: Folk songs with stories; Karaca O?lan; Poet; Poetry